Board Nationality and Educational Diversity and Organizational Performance: A Systematic Review of Literature - Odero, Jackline Akoth; Egessa, Robert (Rescollacom (Research Collaborations Community), 2023)
Board diversity is an important aspect of corporate governance. This paper reviewed research on board nationality and educational diversity and organizational performance in both developed and developing contexts. Further, the paper identified research gaps that may have restricted generalization of the results. The study adopted a qualitative research approach where data was obtained from peer reviewed articles published during the 2010-2022 period. Based on the review most studies revealed that Board nationality and educational diversity influenced firm performance. This study highlights the importance of nationality and educational board diversity. It also offers insights to policy makers so that they can develop, implement and even improve on policies and regulations on board nationality and educational diversity as a way of strengthening board effectiveness thus resulting to organizational performance. The recommendation for firms is to consider nationality and educational diversity when appointing board members.